The Correlation Between Dietary Habits and Dental Hygiene Practice with Dental Caries Among School Children at Urban Area in Semarang - Omaran Ibrahim Mohammed Ali; Oedijani Oedijani; Fatimah Muis (Biosaintifika: Journal of Biology & Biology Education, 2016)
Dental caries is a major cause of tooth loss in children and young adults. Dental caries have been linked to the situation of underprivileged families, nutritional imbalance, and poor oral hygiene techniques, including lack of tooth brushing or flossing the teeth, and also have a genetic etiology. Dietary habits and dental hygiene practice can result in high caries in school children. This research aimed to reveal the correlation between dietary habits and dental hygiene practice with dental caries among school children in urban area of Semarang. The subjects of this research are the elementary student 7 – 9 years old enrolled in schools located in at urban area in Semarang in 2016 and the mother of a student who became the study sample. Data were statisically analyzed usingbivariate analysis and multivariate analysis. Based on the research result, it can be concluded that: there was no correlation between total carbohydrate intake, refined carbohydrate intake, fiber intake, dental hygiene practice with dental caries, bottle feeding and duration of bottle feeding were assosiated with dental cariest-score. Overall, def-t score in the study was very bad with high median of dental caries score and many children have dental caries t-score more than 6.How to CiteAli, O. I. M., Muis, F. O, Oedijani. (2016). The Correlation Between Dietary Habits and Dental Hygiene Practice with Dental Caries Among School Children at Urban Area in Semarang. Biosaintifika: Journal of Biology Biology Education, 8(2), 178-184.